Manajemen Dan Pengelolaan Keuangan Rumah Tangga: Desa Sajau Tanjung Selor - Al Amrie, Machmud; Aspian Nur, Adi; Wiryawan, Dedik (Fakultas Ekonomi Universitas Kaltara, 2022)
There are many strategies that can be taken in order to get around the limitations of household finances due to rising fuel prices, among other spending reductions in strategic posts, such as education, health, including reduction of food quantity and quality of family and debt management. So that they need household financial management that is more efficient in every expenditure, because small problems can become big if not addressed and resolved by wise especially if persolan involving money. The purpose of this study is to describe the impact of rising fuel prices on household finances and how financial management strategies of households after rising the fuel price. The Research was conducted on several families in the Wayhalim Bandar Lampung. The type of research used in this research is qualitative research data collection techniques used include: (1) in-depth interviews and (2) observation. While the data analysis techniques used are data reduction, data presentation and draw conclusions. The analysis showed that they had not properly manage family assets that they have and do not yet have an investment plan. This is indicated by the lack of financial planning for the future and have not applied the financial records (cash flow) that is income less the expenses each month, thus requiring better financial management,namely in terms of both effectiveness and efficiency.